“Só achei uma solução: a ‘morte’” Violência e subjetividade nos escritos de mulheres suicidas (1940 – 1970) - Schneider , Silvia Danielle (2022)
The dissertation presented here analyzes the problem of female suicide in the town of Ponta Grossa, in the Brazilian state of Paraná, in the 1940s, 1950s, 1960s, and 1970s, focusing on the construction of the subjectivity of these women, based on the suicide notes they left, which were found in the judicial archives compiled during the official investigations into their deaths. These documents, the inquests, and the processes were found in the Center for Historical Documentation and Research (the CDPH) of Ponta Grossa State University. During the four decades of the study period, 323 suicides, attempted or induced suicides, and homicide-suicides (attempted or successful) were registered in Ponta Grossa, of which, 92 involved women, with suicide notes being left in 27 cases. The reading of the documents revealed that many suicidal women experienced a long history of violence in their daily lives, some of which was socially acceptable at the time, being considered to be a normal component of everyday, inter-gender relationships. Given the long-term persistence of this scenario throughout the study period, we attempted to understand the link between this violence and the suicides of these women, testing the hypothesis that the suicides were often provoked directly by the violence. To examine this hypothesis in detail, the first chapter presents a general profile of the suicides registered during the study, while the three subsequent chapters describe the experiences of three women – Isabel, Maria and Aurora – whose written narratives explain the motives that led them to end their own lives. These narratives, analyzed in the context of the other documents found in the archives, were the principal sources for the present study, permitting the systematic description and evaluation of the subjectivity and actions of the women as they faced the determinism of their existence. The theoretical-methodological framework for this study was provided by thinkers such as Michel Foucault, Judith Butler, Joan Scott, and Fábio Henrique Lopes. Lopes was a fundamental reference for the understanding of the phenomenon of suicide in this dissertation, in particular by overcoming the taboos that surround it, but also with the objective of comprehending the relationships of power and gender, and the norms and dialogs that determined the subjectivity of each individual – subjugation, but also the control over their own bodies, and ultimately, life and death.